Prevalencia y factores de riesgo asociados a vulvovaginitis en pacientes gestantes hospitalizadas en el Servicio de Gineco-Obstetricia del Hospital Isidro Ayora de Loja. - Jumbo Jadán, Lisbeth del Rocío (2017)
The following study investigation was carried out with the objective to determine the prevalence and risk factors associated with Vulvovaginal problems presented by hospitalized pregnant women in the Gynecological Obstetric Service from Isidro Ayora Hospital in Loja city. A retrospective, descriptive study was performed with a total of 308 patients who met the inclusion criteria. According to the results, the prevalence of Vulvovaginal problems belongs to a 6,17%, of which 62,66% corresponded to Vulvovaginal candidiasis, a 27, 92% to bacterial vaginitis and a 9,42% due to vaginal trichomoniasis. These type of infections were frequently presented in ages between 14 to 25 years of age representing a 50,65% and a 41,23% between 26 to 35 years also predominates in women with a gestational age between 28-41.6 weeks with a 53.25%, in multiparous women with a 61.69%, sexual activity without protection with an 87,34%, the use of synthetic underwear with 83,44% and tight clothes with a 68,51%, with a number of 2-3 sexual partners represented with a 44,16%, for those who took daily vaginal douches from 2 to 4 times with a 20,78; the use of intimate alkaline soaps 19.16%. These findings/results show the main risk factors for Vulvovaginitis and absence of preventive measures, which can serve as clinical markers that allow the detection of diseases in early clinical stages and avoid progression towards severe forms. KEY-WORDS: Vulvovaginitis, prevalence, risk factors.